Age, provenance and tectonic setting from southern portion of the Cuiabá group : implications for the evolution of the Paraguai Belt - Pelosi, Guilherme Francisco Ferreira (2017)
Within the Tocantins Province there is an extensive curved orogenic belt, called the Paraguai Belt, located to the southeast of the Amazonian Craton. This belt is composed of Proterozoic metasedimentary rocks that were folded and metamorphosed during the LateProterozoic Brasiliano cycle. The Cuiabá Group is within the Paraguai Belt, and is divided into 9 subunits, and the uppermost unit, called the Indivisa Subunit, is the focus of this work. The lithotypes found in the Indivisa Subunit are meta-subarkose, arkosic-metagreywacke, schist and hornfels. The sediments are characterized by angular grains and a considerable amount of matrix, demonstrating the immaturity of these rocks and their proximity to the source area. The geochemistry of major elements shows a silica content varying between 68.88% and 79.27% and the graphs for characterization of geotectonic environment plot in the field of passive margin with contribution of active margin source materials. The U-Pb geochronology of detrital zircons shows ages of spanning the entire Proterozoic and into the Meso-Archean, ranging from 601 to 2895 Ma. The ages between 950 and 2895 Ma are consistent with source material derived from the Amazonian Craton. Those detrital zircons between 1800 and 2200 Ma may indicate their source as reworked sediments of the Beneficent Group, and those that comprise ages between 1300 and 2000 Ma may come from reworking the sediments of the Aguapeí Group. The greatest cluster of detrital zircon ages is between 601 and 900 Ma, which does not have corresponding ages in the Amazonian Craton, suggesting that its source comes from east sediments of the deposition basin. The probable sources for the origin of these sediments are the Magmatic Arc of Goiás or the Paranapanema Craton, which serves as the base for the Paraná Basin, and thus, these sediments were probably deposited in a continental margin of the Atlantic type on the Paranapanema Craton.